Development of Culinary Tourism Destinations Based on Local Wisdom and Social Media (A Case Study of Do-Dolan Kampung, Lumajang) - Heyin Krida Laksono; Siti Asiyah; Dwiyani Sudaryanti (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study explores the development strategy of Do-Dolan Kampung as a sustainable culinary tourism destination based on local wisdom and analyzes the role of social media in promoting tourism without compromising cultural values. The goal is to enhance the welfare of the community in Ditotrunan Village, Lumajang. A descriptive qualitative approach with a case study method was used. Data were collected through interviews, participatory observation, document analysis, and focus group discussions. SWOT analysis was applied to assess management and promotional strategies via social media. The findings show that Do-Dolan Kampung successfully promotes local wisdom-based culinary tourism through strong community participation and creative use of social media. Social media has proven effective in increasing tourist attraction while preserving cultural values. However, challenges persist in terms of infrastructure, digital literacy, and the risk of cultural commercialization. This research contributes theoretically by integrating local wisdom and digital strategies within the framework of community-based tourism. Its originality lies in focusing on a small, self-managed urban tourism destination that emphasizes cultural identity as its main appeal. The Do-Dolan Kampung model serves as a good example for other villages or districts aiming to develop tourism based on local wisdom and support for MSMEs. Practically, this study offers strategic insights for tourism managers and local governments to develop sustainable, culturally sensitive tourism. However, the research is limited to a single site and uses a qualitative approach, which restricts the generalizability of the findings. Limitations in time and access to digital data also posed challenges in evaluating the full impact of social media promotions.